A Collaborative Governance dan Penerapannya dalam Kebijakan Penanganan Stunting di Kota Samarinda - Maulidah, Maulidah; Paselle, Enos; Henly Putri, Annisa Asri; Ernita, Lina; Indriani, Eny Agus; Yunus, Muhammad; Yuliana (Universitas Medan Area, 2024)
This study aims to describe the application of Collaborative Governance in Stunting Handling Policy in Samarinda City. This research is important to do because the success achieved by a collaboration can reflect the readiness of stakeholders to overcome problems that exist in the community. This research uses descriptive techniques with a qualitative approach. The research was conducted in Samarinda City, East Kalimantan using the theory of 5 stages of collaboration by Tirell and Clay, and 8 criteria for successful collaboration by De Seve. Data collection techniques are carried out through interviews, observation, and documentation. The data analysis technique used is according to Miles and Huberman. The results showed that the implementation of Collaborative Governance in the Stunting Handling Policy in Samarinda City is still not running optimally. This can be seen through the obstacles of one of the criteria in De Seve's 8 criteria for successful collaboration. The obstacles faced are that there are still policymakers who do not understand their role in stunting reduction efforts, and there are still silos of mentality between parties involved in stunting reduction in the city of Samarinda. Collaboration that has not been optimal has resulted in the Samarinda City Government has not been able to reduce the prevalence of stunting in Samarinda City.